The Making of a Cop - Rachlin, Harvey (New York Pocket Books, 1991)
An accurate account of the rigorous discipline and intensive instruction in the New York police academy and of how that training changes the lives of the young men and women who will soon be out there on the streets.
Keywords: The Making of a Cop -- Social Science -- Police training -- New York (State)--New York